Formulation and Test of Antibacterial Activity Gel Mask Peel Off Stem and Suruhan Leaves (Peperomia Pellucida L.) Extract Against Propionibacterium Acne - Farid, Nurfiddin; Dwi Rantisari Thayeb, Andi Meinar; Sulfiani, Sulfiani; Saleh, Adriandy (Sean Institute, 2022)
Stems and leaves of suruhan (Peperomia Pellucida L.) contain compounds belonging to the class of flavonoids, alkaloids, tannins, phenols, terpenes and essential oils which have potential as antibacterials. This study aimed to find out whether the stem and leaf extracts of suruhan (Peperomia pellucida L.) can be formulated into a gel peel-off mask preparation that is physically and chemically stable, and can inhibit the acne-causing bacteria Propionibacterium acne. This study used a laboratory experimental method, namely the formulation of Peel off gel mask preparations of stem and leaf extracts with different base concentration variations. Testing the characteristics of the preparation which includes organoleptic test, homogeneity, spreadability test, pH test, drying time test, viscosity test using the cycling test method and for antibacterial activity test using the well diffusion method. The results showed that the gel peel-off mask preparation of suruhan stem and leaf extract (Peperomia pellucida L.) fulfilled the requirements for the characteristics of the preparation both physically and chemically, and could inhibit the growth of acne-causing bacteria (Propionibacterium acne) at a concentration of 2% (15.1 mm), 3%, (17.8 mm) and 4% (19.4 mm) in the zone of strong inhibition. It can be concluded that formulation gel mask preparations Peel off stems and leaves of suruhan (Peperomia pellucida L.) can provide antibacterial activity against Propionibacterium acne with respective inhibition zones of 15.1 mm, 17.8 mm and 19.4 mm which are equally strong in inhibiting Propionibacterium acne bacteria